Influences of cosmic radiation, artificial radioactivity and aerosol concentration upon the fair-weather atmospheric electric field in Lisbon (1955–1991) - Serrano, Claudia (2012)
The atmospheric electric field is influenced by cosmic radiation, radioactivity and aerosols. In this work we investigate the existence of: (i) correlations between relative anomalies of annual values of atmospheric electric field and cosmic radiation intensity, artificial radioactivity and aerosol concentration; (ii) seasonal correlations between relative anomalies of the atmospheric electric field and cosmic radiation intensity. We used data of the electric field strength recorded at the Portela meteorological station (Lisbon) in the period 1955–1991. We found statistically significant inverse correlations between atmospheric electric field and cosmic radiation in the period 1967–1991. We also found that the influence of cosmic radiation on the atmospheric electric field is strong in wintertime and very weak in summertime. The GCR–CN–CCN–Cloud Hypothesis and the wintertime reduced boundary layer convection are analyzed as possible explanations for this difference.